2019
DOI: 10.3892/ol.2019.10294
|View full text |Cite
|
Sign up to set email alerts
|

STAT6 phosphorylation upregulates microRNA‑155 expression and subsequently enhances the pathogenesis of chronic lymphocytic leukemia

Abstract: Chronic lymphocytic leukemia (CLL), a clonal expansion of CD5 + B cells, is the most common form of adult leukemia; however, the molecular mechanisms underlying its pathogenesis remain undetermined. It has been previously suggested that numerous biological factors, including cytokines, may be involved in the proliferation of malignant cells. For example, interleukin (IL)-4, IL-2, interferon-γ and tumor necrosis factor serve roles as inhibitors of cellular apoptosis; whereas IL-5 and IL-10 are inducers of cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
3
Order By: Relevance
“…Furthermore, miR-144-5p, another isoform of miR-144, directly targets Sdc3 in renal cell carcinoma (Rcc) to inhibit the cancer cell growth (31). Additionally, the study by chen et al demonstrated that the low expression of miR-144-3p contributes to the prediction in lung cancer patients (32). These previous studies support the important roles of miR-144-3p in different types of cancer.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, miR-144-5p, another isoform of miR-144, directly targets Sdc3 in renal cell carcinoma (Rcc) to inhibit the cancer cell growth (31). Additionally, the study by chen et al demonstrated that the low expression of miR-144-3p contributes to the prediction in lung cancer patients (32). These previous studies support the important roles of miR-144-3p in different types of cancer.…”
Section: Discussionmentioning
confidence: 77%
“…Many miRs are considered as factors influencing CLL risk and prognosis, among others miR-155-5p. The expression of this miR is upregulated and associated with higher disease risk and poorer prognosis [ 29 31 ]. The influence of miRs' epigenetic regulation of BTLA protein expression is the subject of our ongoing study.…”
Section: Discussionmentioning
confidence: 99%
“…Sự phosphoryl hóa STAT5 làm khởi phát bệnh đồng thời duy trì sự sống của tế bào ung thư (Hantschel et al, 2012). Hoạt hóa tín hiệu phân tử STAT6 cũng làm tăng nguy cơ mắc bệnh ung thư máu (Chen et al, 2019b). Ngoài ra, các nghiên cứu về phân tử tín hiệu nuclear factor κB (NF-κB) cũng rất được chú ý. Khi tế bào ở trạng thái nghỉ, NF-κB tương tác với các protein ức chế là IκB trong đó có IκB-α.…”
Section: Tóm Tắtunclassified
“…Tương tự với các nghiên cứu về ung thư trước đó (Meissl et al, 2017;Chen et al, 2019b), chúng tôi cũng chỉ ra rằng, mức độ biểu hiện của STAT1 và STAT6 ở bệnh nhân CML cao hơn so với người khỏe mạnh. STAT6 biểu hiện tăng cao trong các dòng tế bào có nguồn gốc từ những u lympho Hodgkin.…”
Section: Biểu Hiện Một Số Gen Tín Hiệu Trên Bệnh Nhân CMLunclassified